Nuclear Materials - Tsvetkov, Pavel V. (IntechOpen, 2021)
This book examines nuclear materials through select chapters focusing on the impact of reactor technology, use of materials data in modeling applications, and reasoning in design choices. It provides an opportunity to explore contemporary and emerging frontiers. Chapters cover such topics as manufacturing approaches, forms, fundamental considerations, and applications as well as highlight contemporary pathways in nuclear material development.